2015
DOI: 10.1007/s10072-015-2290-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dystrophin gene in Iranian Duchenne and Becker muscular dystrophies patients and identification of a novel mutation

Abstract: Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are the most frequent muscular dystrophies. Present study aimed to determine the frequency of dystrophin gene alterations in Iranian DMD/BMD patients using molecular techniques. 146 Iranian DMD/BMD patients have been analyzed using two devised sets of multiplex polymerase chain reaction (M-PCR) followed by multiple ligation-dependent probe amplification (MLPA). Two isolated DMD and BMD patients were analyzed by DNA sequencing. 30.9 % of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Exon 44 was the most frequently deleted single exon in the present study, while other studies reported exons 45 and 51. Among multiexon deletions in this study, exons 45–50 and exons 45–52 were the most commonly involved exons, which is consistent with the results of previous studies [ 29 , 30 ]. The largest deletion found in our study extended from exon 3 to exon 44 in the proximal part, while the largest deletion in previous studies was found in exons 8–47.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Exon 44 was the most frequently deleted single exon in the present study, while other studies reported exons 45 and 51. Among multiexon deletions in this study, exons 45–50 and exons 45–52 were the most commonly involved exons, which is consistent with the results of previous studies [ 29 , 30 ]. The largest deletion found in our study extended from exon 3 to exon 44 in the proximal part, while the largest deletion in previous studies was found in exons 8–47.…”
Section: Discussionsupporting
confidence: 93%
“…Analysis of the distribution of mutation sites in 79 exons revealed that 47.4% of them were in the distal part, 35.5% were in the proximal part, and 1.3% were in both distal and proximal parts. Distal deletions constituted 57% of deletions in DMD, and their distribution was compatible with previous reports ([ 24 , 30 ], and [ 29 ]).…”
Section: Discussionsupporting
confidence: 92%
“…No novel mutations were identified in this study. In a study in Iranian DMD/BMD patients, 30.9 % of patients had single exon deletion, while group and contiguous exon deletions were identified in 41% of the patients [12]. The most numerous exon deletions included exons 45-50, and two exons 3-5 and 41-43 duplications (1.4 %) was observed in a BMD and a DMD patient, respectively [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several isolated deletions of exon 49 of DMD have already been reported in the literature associated with both DMD and BMD phenotypes [ 18 , 19 , 20 , 21 , 22 , 23 ] ( Table S1 ). Notablythese reports did not include any specific phenotypic information about disease severity.…”
Section: Discussionmentioning
confidence: 99%